Sexuality, parent-adolescent communication, and parental involvement laws: implications for family life educators and policy - Bishop, Erin Renae (Kansas State University, 2008)
This is a review of the body of literature about teenage sexuality, pregnancy, abortion, parent-adolescent communication, and parental involvement laws. The literature review focused on current United State's policies on teenage abortion and the effects of parental involvement laws and judicial bypass. A review of other nations' policies regarding teenage sexuality, pregnancy, and abortion and the outcomes of these policies is given and compared to the policies of the United States. Proponents' reasons for parental involvement laws are explored. Current research on the effects that parental involvement laws have on adolescents and their families, adolescents' abilities to make informed decisions about abortion, and characteristics of teenage girls who choose abortion is reviewed. The need for more research on teenage sexuality, parent-adolescent communication, and the effectiveness of parental involvement laws are identified. Implications for family life educators for the prevention of teenage pregnancy as well as interventions for family life educators in the event of adolescent pregnancy and abortion are provided. Implications for the need to review current parental involvement policies and the need to apply research to these policies are also recommended.
Keywords: Parental involvement laws; Abortion; Parent-adolescent communication; Family life education; Sexuality; Adolescent; Women's Studies (0453)